ENGLISH MATERIAL DEVELOPMENT BASED ON SCIENTIFIC APPROACH: A CONTENT ANALYSIS OF âWHEN ENGLISH RINGS A BELLâ COURSE BOOK - Nimasari, Elok Putri (Kajian Linguistik dan Sastra, 2016)
Government has launched the 2013 curriculum four years ago. It becomesone of interests to be investigated. Pros and cons have been raised toward thisnew implemented curriculum. In 2014, a revision of the 2013 curriculum coursebook entitled âWhen English Rings the Bellâ had been done. A content analysisstudy is needed toward the implementation of the 2013 curriculum for the sake ofmaterial development. This study aims to investigate whether or not the revisedof the 2013 curriculum course book entitled âWhen English Rings a Bellâ is inline with the theory of scientific approach. This study used qualitative descriptivemethod to describe the results.